Electroacupuncture at ST36-ST37 and at Ear Ameliorates Hippocampal Mossy Fiber Sprouting in Kainic Acid-Induced Epileptic Seizure Rats - Liu, Chung-Hsiang (Hindawi Publishing Corporation, 2014)
Our previous study showed that mossy fiber sprouting can occur in the hippocampus region in rats 6 wk after kainic acid-induced epileptic seizure, and this mossy fiber sprouting can facilitate epileptogenesis. Transcutaneous auricular vagal nerve stimulation (VNS), which is similar to cervical VNS, can reduce the occurrence of epileptic seizure in intractable epilepsy patients. Greater parasympathetic nerve activity can be caused by 2 Hz electroacupuncture (EA). Therefore, we investigated the effect of 2 Hz EA at ST-36-ST37 and at the ear on mossy fiber sprouting in kainic-treated Sprague-Dawley rats. The results indicated that applying 2 Hz EA at ST36-ST37 and at the ear for 3 d per week over 6 consecutive weeks can ameliorate mossy fiber sprouting in the hippocampus region of rats. These results indicated that applying 2 Hz EA at ST36-ST37 and at the ear might be beneficial for the treatment and prevention of epilepsy in humans.